Accentuated polymorphism of heterochromatin and nucleolar organizer regions in Astyanax scabripinnis (Pisces, Characidae): tools for understanding karyotypic evolution - Mantovani, M.; Abel, LDD; Mestriner, C. A.; Moreira, O. (Kluwer Academic Publ, 2000)
Astyanax scabripinnis has been considered a species complex because it presents high karyotypic and morphological variability among its populations. In this work, individuals of two A. scabripinnis populations from different streams in the same hydrographic basin were analyzed through C-banding and AgNOR. Although they present distinct diploid numbers, they show meta and submetacentric chromosome groups highly conserved (numerically and morphologically). Other chromosomal characteristics are also shared by both populations, as the pattern of constitutive heterochromatin distribution (large blocks in the telomeric regions of subtelocentric and acrocentric chromosomes) and some nucleolar chromosomes. Inter-individual variations both in the number and size of heterochromatic blocks, and in the number and localization of NORs were verified in the studied populations, characterizing them as polymorphics for these regions. The mechanisms involved in the dispersion of heterochromatin and NORs through the karyotypes, as well as the possible events related to the generation of polymorphism of those regions are discussed. Furthermore, relationships between these populations and within the context of the scabripinnis complex are also approached.
Keywords: Astyanax scabripinnis; constitutive heterochromatin; karyotypic evolution; nucleolar organizer regions (NORs); polymorphism